KONSEP PENGEMBANGAN FITRAH BAKAT PADA JENJANG PENDIDIKAN SMA DI AB HOME BOGOR - Natasya Aisyah Putri; Suhendra Suhendra; Yono Yono (Universitas Pahlawan Tuanku Tambusai, 2022)
The urgency of talent development is to enable each individual who is unique within him or her, to recognize and wisely utilize their potential to fulfill their mission as Caliph on Earth. The task of the Khilafah is to guide all of God's creation, both animate and inanimate, to the purpose of its creation. When a person is born into this world, Allah gives them a series of fitrah to accompany them. Part of the nature that people have from birth is the nature of talent. In Law Number 20 of 2003 concerning the National Education System, the objectives and functions of education are stated in accordance with the purpose of human creation, namely education aims so that the potential possessed by students can be developed and become human beings who believe and fear God Almighty, have noble character. , healthy, knowledgeable, capable, creative, independent, and become a democratic and responsible citizen. The purpose of this study was to determine the concept of talent development at the high school level at AB Home and how to apply talent development at the high school level at AB Home. This study adopted a qualitative approach. The findings obtained from the results of this study indicate that the application of the concept of developing talent at AB Home has existed since 2015 when AB Home was founded. In practice, talent development is carried out through talent-based projects. Therefore, AB Home's academic portion is 40% less than the project activity portion of 60%. Projects undertaken are divided into three categories: personal projects, projects units, and organizational projects. The obstacles usually occur because children do not understand themselves, parents' lack of understanding of the concept of developing talent, and children's acceptance of their talents can lead to a lack of effectiveness in developing natural talents. The solution to overcome these obstacles is to provide the necessary facilities and infrastructure in the process of continuing learning, following educational developments and developing various talents. In addition, the solution is also done by communicating with parents and not forgetting to communicate with children. Keywords: Talent Managament, fitrah, talent